Teaching Evaluation in the point of View of Physical Education Teachers’ Teaching Gymnastics in Primary Learning Stage in Nablus - Abdelhaq, Emad (Jordan Journal of Educational Sciences, 2005)
The purpose of this study was to evaluate teaehing in the point of view of Physical education teachers’ teaching Gymnastics in primary schools in Nablus, and to determine the differences according to gender, educational level, and experience variables. The sample of the study consisted of (80) male and female teachers’ and they were divided equally in to groups of 40 teachers each. The results revealed a very high degree of evaluation for the learning domain, and high degree for class administration and total score of effectiveness, while the degree was moderate for both career duties and evaluation. Also, the results revealed that there are no significant differences at ( α = 0.05) in teaching due to experience and gender while the evaluation of a significant difference was there according to educational level in favor of the highest qualification. Based on the findings the researcher recommended implement such behaviors by supervisors in workshop and teachers evaluation processes.